Explaining the diversity in Malay-English code-switching patterns: the contribution of typological similarity and bilingual optimization strategies - Treffers-Daller, Jeanine; Majid, Sheikha; Thai, Yap Ngee; Flynn, Naomi (Multidisciplinary Digital Publishing Institute, 2022)
Bilingual speakers often engage in code-switching, that is the use of lexical items and grammatical features from two languages in one sentence. Malaysia is a particularly interesting context for the study of code-switching because Malay-English code-switching is widely practiced across formal and informal situations, and the available literature reveals that there is a great diversity in switch patterns in this language pair. One of the most remarkable characteristics of Malay-English code-switching is the high frequency of switches of function words (pronouns, modal verbs, demonstratives, etc.), which is very unusual in most code-switching corpora. Here, we analyse the structural properties of Malay-English code-switching, which have received less attention than functional analyses in the academic literature on code-switching in this language pair. We first summarize the literature on the different types of code-switching that are found in a range of sources, and then analyze the code-switching patterns in the speech of two teachers of English in Malaysia. We conclude with a discussion of the variables that can explain the diversity found, in particular structural factors (similarity between the word orders of both languages, and the limited number of inflections), and bilingual optimization strategies, as well as strategies of neutrality and efficiency.